Ursolic Acid Treatment Alleviates Diabetic Kidney Injury By Regulating The ARAP1/AT1R Signaling Pathway - Ma TK; Xu L; Lu LX; Cao X; Li X; Li LL; Wang X; Fan QL (Diabetes, Metabolic Syndrome and Obesity, 2019)
Tian-Kui Ma,1,* Li Xu,1,2,* Ling-Xu Lu,1,3,* Xu Cao,1 Xin Li,1 Lu-Lu Li,1 Xu Wang,4 Qiu-Ling Fan1 1Department of Nephrology, The First Hospital of China Medical University, Shenyang, Liaoning, People’s Republic of China; 2Department of Clinical Laboratories, The First Hospital of China Medical University, Shenyang, Liaoning, People’s Republic of China; 3The First Respiratory Department, General Hospital of Fushun Mining Bureau, Fushun, Liaoning, People’s Republic of China; 4Department of Gastroenterology, The First Hospital of China Medical University, Shenyang, Liaoning, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qiu-Ling Fan Email cmufql@163.comPurpose: This study aimed to investigate whether ursolic acid (UA) mitigates renal inflammation, oxidative stress and fibrosis by regulating the angiotensin II type 1 receptor-associated protein (ARAP1)/angiotensin II type 1 receptor (AT1R) signaling pathway and subsequently alleviating renal damage.Methods: db/db mice were divided randomly into a diabetic nephropathy (DN) group and a UA treatment group. Light microscopy and electron microscopy were used to observe pathological changes in renal tissues. Immunohistochemistry (IHC) was employed to examine changes in the expression of ARAP1, AT1R, 8-hydroxydeoxyguanosine (8-OHdG), NADPH oxidase 2 (NOX2), the extracellular matrix protein fibronectin (FN), IL-1β and IL-18 in renal tissues. Western blotting and RT-qPCR were used to detect the respective changes in the protein and mRNA levels of ARAP1, AT1R, NOX4, NOX2, transforming growth factor-β1 (TGF-β1), FN, collagen IV, IL-1β and IL-18 in renal tissues and mesangial cells. In addition, immunofluorescence staining was employed to examine changes in FN and NOX2 expression in mesangial cells.Results: UA treatment effectively reduced the body weights and blood glucose levels of db/db mice (p<0.05) as well as the urinary albumin/creatinine ratio (p<0.05). In addition, the renal tissue lesions and glomerulosclerosis index of the db/db mice were significantly improved after treatment (p<0.01). Histochemical analysis results showed significantly lower expression levels of ARAP1, AT1R, FN, NOX2, 8-OHdG, IL-1β and IL-18 in renal tissues in the UA treatment group than in the DN group. Western blotting and RT-qPCR data also revealed UA-induced decreases in the renal levels of the ARAP1, AT1, NOX4, NOX2, TGF-β1, FN, collagen IV, IL-1β and IL-18 proteins in vivo and/or in vitro (p<0.01). ARAP1 knockdown effectively reduced the expression of NOX2 and FN in vitro.Conclusion: UA alleviated renal damage in type 2 diabetic db/db mice by downregulating proteins in the ARAP1/AT1R signaling pathway to inhibit extracellular matrix accumulation, renal inflammation, fibrosis and oxidative stress.Keywords: ursolic acid, diabetic nephropathy, oxidative stress, renal fibrosis, ARAP1, AT1R